Pelanggaran Perjanjian Internasional Secara Diam-Diam Dan Akibat Hukumnya - Filianthino Eurico Wattimena; Josina Agustina Yvonne Wattimena; Welly Angela Riry (Faculty of Law Universitas Pattimura, 2023)
International agreements play a very important role in regulating relations and life between countries. Indonesia is one of the countries that made a bilateral agreement with Australia regarding the regulation of traditional fisheries rights through the 1974 MoU Box agreement. However, in reality, in implementing its traditional fisheries rights, problems were found in the form of obstacles caused by unilateral violations by Australia of the agreement contained in the contents of the MoU Box. . The research method used in the research is normative juridical, using a research approach, namely the statutory approach, concept approach and case approach. The results of the research show that in fact violations of the agreement between Indonesia and Australia occurred secretly by Australia. Proof of the violations committed by Australia was the issuance of the 1981 MoU which canceled the 1974 MoU which previously determined the fishing area from 12 miles to 200 miles. The changes to the agreement were not notified to Indonesia as one of the countries that made an agreement with Australia. The legal consequence that arises is that traditional fishermen whose rights are recognized in UNCLOS 1982 can no longer fish in this area, because Australia has unilaterally designated this area as a conservation area. Indonesia will also consider Australia as a country that is inconsistent in implementing bilateral agreements between the two countries regarding the recognition of the traditional rights of fishermen and this will have an impact on diplomatic relations between the two countries.